Improvement of Solenoid Valve Performance by Axial Slots Inserted in the Armature - GORAJ, Robert (Engineering Transactions, 2017)
The article presents numerical investigations of the influence axial slots inserted in the armature of a solenoid valve (SV) on the magnetic and frictional force acting on the armature during its movement. The numerical computations were performed using the method of finite differences. The computational room of the magnetic solution was the radial air gap of a SV. In the case of the fluid mechanical solution the computation room was the oil film. Both of these rooms were functions of the circumferential position of the armature. These computational rooms were transformed to the co-ordinate system in each they get a rectangle. This transformation was performed by means of the Laplace operator derived using a function shoal and the differential geometry. The computed distributions of magnetic energy density in the radial air gap and the magnitude of the magnetic flux density on the side surface of the eccentrically positioned armature in the magnet yoke were presented and discussed. These distributions in the case of both slotted and non-slotted armature were visualised in the transformed coordinate systems and compared to one another. Also the distribution of the oil velocity in the oil film and the distribution of the shear stress vector at two different temperatures were shown in figures.